Analisis Keberlanjutan Lingkungan Melalui Capaian Pertumbuhan Ekonomi Dan Konsumsi Energi Terbarukan Di Indonesia - Nadira Rahmandani; Raditya Sukmana (STIE Mandala Jember, 2023)
This study aims to determine the effect of economic growth and renewable energy on environmental sustainability in Indonesia. By applying the VECM analysis technique and data from 1990-2018 it was found that in the long term economic growth, renewable energy and natural resource extraction have an effect on environmental sustainability. The use of ecological footprint indicators is the main focus in this study because there are still very few studies that describe environmental sustainability in Indonesia from the perspective of the ecological footprint. This research provides impetus for the government to continue to strive for better renewable energy by seeing how important it is for environmental sustainability in Indonesia